Synthesis of Thiol-Modified Hemicellulose, Its Biocompatibility, Studies, and Appraisal as a Sustained Release Carrier of Ticagrelor - Zaman, Muhammad; Bajwa, Rabia Imtiaz; Qureshi, Omer Salman; Rehman, Atta Ur; Saeed, Sadaf; Amjad, Muhammad Wahab; Ghafoor Raja, Maria Abdul; Hussain, Muhammad Ajaz (Frontiers in Pharmacology, 2021)
Background: Nature has always been considered as the primary source of pharmaceutical ingredients. Variety of hemicelluloses, as well as their modified forms have been under investigation. Herein, a study has designed to explore the biocompatibility as well as potential of hemicellulose and its modified form (thiolated hemicellulose) as pharmaceutical excipient. Method: For thiol modification thiourea was used as thiol donor, HCl as catalytic reagent and methanol for washing purpose. Modified polymers were characterized for both physicochemical characteristics including, surface morphology, amorphous or crystalline nature of the particles, modification of polymer by FTIR and biocompatibilities. For acute oral toxicity study, a single dose of 2g/kg was administered to the albino rats of 200g average weight (n=3). Polymers were evaluated as pharmaceutical excipients by preparing compressed tablets of antiplatelet drug (Ticagrelor), followed by various quality control tests, such as, swelling index, thickness and diameter, disintegration and in-vitro drug release. Results: From the results it was observed that thiol modification has been successfully accomplished as characteristic peaks belonging to –SH group were appeared at 2667.7691 cm-1 in FTIR scan. The modified polymer was found safe in the use concentration range, confirming their safe use for in vivo analysis. No significant effect has been observed in the behavior, biological fluid (blood) or on vital organs. Thiolated hemicellulose was found to be excellent drug retarding polymer as 8hrs of dissolution studies showed that 67.08 % of the drug has been released. Conclusion: Conclusively, incorporation of thiol moiety made the polymer more mucoadhesive with and worthy carrier of the drug with good biocompatibilities